Financial inclusion to build economic resilience in small-scale fisheries. (August 2020) - Pomeroy, Robert; Arango, Carlos; Lomboy, Cristopher G.; Box, Steve
Abstract: Lack of access to financial services leaves fishing households and their fishing businesses with limited options to obtain financing and manage cash flow for family expenses or business investments. The lack of access is filled by informal lenders that can also be the primary buyers of fish or the owners of the boats. For rural fishing households, access to formal financial services, also known as financial inclusion, can bring increased financial resilience to the household. The paper reviews the current barriers to financial inclusion of small-scale fishing households such as limited financial capability and literacy, lack of assets for collateral, geographic distance from a financial institution and lack of formal identification. It also discusses solutions to address these barriers including financial literacy, de-risking financial institutions, financial data collection, provision of a range of financial services besides credit, and understanding the client that will enable fishing households to retain control over their earnings and savings. Financial inclusion can help reduce the different vulnerabilities of poor fishing households and rural communities and lead to improved economic resilience.